APPLICATION OF TEXTURE SCHEMES IN ARCHITECTURAL DRAWING AN ANALYTICAL STUDY –FIRST YEAR STUDENTS’ DRAFTS IN DEPARTMENT OF ARCHITECTURE IN UNIVERSITY OF DUHOK - BARAKAT, ARMANGE ISMAEL (Journal of Duhok University, 2017)
The determination of schemes of texture considered an essential need to get a full understanding of the research problem which represented by the lack of clarity about the role of texture characteristics which adopted in forming the texture schemes in architectural drawing. In architectural design the texture strengthens our understanding of quality of form, in addition to that texture can help students acquire unique visual features in their drafts. Accordingly, this paper focuses on studying the texture characteristics in architecture and how the students can use these characteristics to create their textures. So this paper aims to explore the possibilities of texture schemes that used in architectural drawing. The first year students’ drafts in the department of architecture have been analyzed using geometrical methods to define the strategies for putting texture schemes of these drafts. The results showed that the students adopted a set of characteristics of texture more than others in their schemes. The characteristics have been used on two levels: the first one is the micro level related to texture motifs, which work to generate the texture structure that represents the macro level of the scheme. This paper provides a vision about the importance of texture characteristics such as motifs shape, motifs scale, the natural pattern of motifs and directionality of motifs, at the first level and at the second level the types of texture, the roughness of texture, texture reflection and texture relation that have been used. The focus has been on forming the texture wheel, which in turn gives the students ideas about other characteristics of texture and helps to use them in their work.